Foreign aid and democratization in developing countries - Resnick, Danielle (Oxford University Press, 2018)
This article examines how donors influence democracy through foreign aid. Focusing on development aid and democracy assistance, it considers three mechanisms through which aid is disbursed: the diffusion of norms and knowledge, the provision of incentives, and the use of coercion. The article first looks at different types of foreign aid before providing a conceptualization of the democratization process. It then discusses the mechanisms linking different types of aid with elements of democratization and how well these mechanisms have worked in practice. It argues that coercion has been most conducive at influencing democratic transitions and addressing breakdown. Norms and knowledge diffusion as well as incentives are more directly influential, in both positive and negative ways, on issues of accountability and competitive party systems.